Gender pay gaps in the social sciences - Ayelet Gneezy; Uri Gneezy; Joshua Graff Zivin; Gaurav Khanna; Elizabeth Lyons; Marta Serra-Garcia (Proceedings of the National Academy of Sciences, 2026)
We provide a longitudinal, multifield analysis of the gender pay gap in academia that directly links individual-level salaries to measures of scholarly productivity. Using administrative data from the ten campuses that comprise the University of California system, we combine detailed pay records with bibliometric data on publications and citations for faculty in five major social science fields. We find a raw gender pay gap of 23%, which decreases to 4.3% after controlling for field, campus, and cohort. Including controls for job title and scholarly productivity has little effect on the estimated gap, although they substantially increase explanatory power. A decomposition shows that 17% of the gap is unexplained, persisting across junior and senior faculty. We also find a large, persistent gender gap in publications, but no citation gap once output and career length are considered. Field-level analysis reveals that pay gaps are not universal: They persist in Business, Sociology, and Anthropology, but are absent in Economics, Political Science, and smaller social science fields. Our results suggest that pay transparency is insufficient to eliminate salary disparities and that more equal representation within the field is not a prerequisite for pay equity. Our study isolates the residual gap that remains unexplained by productivity or seniority, challenging the view that these factors fully account for gender pay differences. Taken together, our findings highlight the role of field-specific norms and institutional structures, offering directions to promote equitable compensation in academia.